INCENTIVADORES RESPIRATÓRIOS NA EXPANSÃO PULMONAR: UMA REVISÃO SISTEMÁTICA (Movimenta (ISSN 1984-4298), 2022)
Lung reexpansion therapy is a physical therapy approach that aims to increase lung volumes, using techniques and/or instruments that encourage the patient to inhale deeply, with incentive spirometry (IS) being one of the strategies. The IS is a mechanical device aimed at expanding alveolar units. They provide visual feedback, giving the patient a measurable goal while performing deep breathing. There are two types of IS, the volume-oriented incentive spirometer (ISV) and the flow-oriented incentive spirometer (ISF), both of which are used to encourage the patient to inhale to full lung capacity. This study aimed to verify the effects of IS on lung expansion through a systematic literature review. A systematic review was carried out, by articles classified as randomized clinical trials, cross-sectional studies, crossovers and control cases, in the PubMed, BVS, Lilacs, Scielo, Scopus, Cochrane Library and PEDro databases. The initial sample consisted of 325 studies, after all the search criteria were performed, 17 articles were included for analysis. Concluding that in the articles that evaluated the use of IS in individuals who underwent postoperative surgeries, it proved to be inconclusive in lung expansion, in neurological individuals, despite the majority of the results being positive, a careful analysis should be considered. In healthy individuals and in other conditions, its use proved to be effective. Thus, showing that there is no consensus on the effectiveness of IS in lung expansion. However, more studies must be carried out.